2, 3-Di-O-picolinyl building blocks as glycosyl donors with switchable stereoselectivity. Issue 11 (25th February 2016) - Yasomanee, Jagodige P.; Parameswar, Archana R.; Pornsuriyasak, Papapida; Rath, Nigam P.; Demchenko, Alexei V.
Abstract : Coordination of 2, 3-di- O -picolinyl protected glycosyl donors with PdBr2 allows to "switch" the stereoselectivity of glycosylations from β- to α-. Abstract : 2- O -Picolinyl protected glycosyl donors lead to the formation of 1, 2- trans glycosides with complete stereoselectivity. This is due to the participatory effect of the picolinyl nitrogen that is able to block the bottom face of the ring via a six-membered cyclic intermediate. Herein we demonstrate that if the nitrogen atom of the O -picolinyl moiety is temporarily blocked by coordination to the metal center (Pd), it becomes unavailable to participate in glycosylation and hence the stereoselectivity of 2- O -picolinyl-assisted glycosylations can be "switched".